Design and Stiffness Analysis of 3-（2SPS） Parallel Machine Tool - Wantao Xiong; Kaiming Li (Jixie chuandong)
The 3-（2SPS） parallel machine tool is taken as the main research object， the 3D solid model is established by using SolidWorks software. On this basis， the machine coordinate system is first established， and the Jacobian matrix and the parallel machine tool stiffness matrix are obtained. Using MATLAB programming， under the three working conditions， the simulation stiffness of the parallel machine tool is distributed according to the position of the platform. Then the ANSYS Workbench software is used to carry out the finite element analysis of the machine tool. Under the same working conditions， the overall displacement cloud image and the finite element simulation stiffness of the machine tool are obtained. The two analysis results prove the validity of the simulation results and lay a foundation for the subsequent optimization and good dynamic performance of the machine tool.